2021
DOI: 10.1177/10690727211063372
|View full text |Cite
|
Sign up to set email alerts
|

Career Goal Discrepancy, Career Distress, and Goal Adjustment: Testing a Dual Moderated Process Model in Young Adults

Abstract: Identifying a large discrepancy in young people’s career goal progress can lead to distress, activating meaning-making, self-regulatory mechanisms aimed at resolving the uncomfortable situation. We assessed these important career-regulatory processes in a theoretical model by testing the indirect effects of career goal discrepancy on goal adjustment (assimilation and accommodation) via career distress, and assessed the conditionality of these effects based on two moderators (career calling and negative career … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 45 publications
1
17
0
1
Order By: Relevance
“…The 12-item Career Goal Progress Discrepancy Scale (Creed & Hood, 2015) assesses discrepancy related to career achievement, effort, set standard and ability (e.g., ‘I am not sure I am capable of meeting the requirements for the career I really want’). It has been used with young adults (Creed et al, 2015; Praskova & McPeake, 2021). The authors reported an α of .96 (current α = .96) and evidence for validity based on lower career goal commitment and higher career distress.…”
Section: Methodsmentioning
confidence: 99%
“…The 12-item Career Goal Progress Discrepancy Scale (Creed & Hood, 2015) assesses discrepancy related to career achievement, effort, set standard and ability (e.g., ‘I am not sure I am capable of meeting the requirements for the career I really want’). It has been used with young adults (Creed et al, 2015; Praskova & McPeake, 2021). The authors reported an α of .96 (current α = .96) and evidence for validity based on lower career goal commitment and higher career distress.…”
Section: Methodsmentioning
confidence: 99%
“…During the transition from school to full-time employment, university graduates are likely to suffer from career distress. In current literature, several factors have been recognized as antecedents of career distress, encompassing career indecision, career incongruence, career compromise, poor career preparation, and underdeveloped vocational identity, career goal discrepancy, discrepancy between adolescent-set and parent-set career goals (Creed et al, 2016; Creed & Gagliardi, 2015; Praskova & McPeake, 2022; Sawitri et al, 2021). However, relatively little work has examined factors that reduce career distress for young people.…”
Section: Literature Reviewmentioning
confidence: 99%
“…49 Employees who possess career calling are better at self-regulation and adjusting their career goals, effort, strategies and personal emotions. 46,50 If an individual fails to live their calling, it is difficult for them to obtain rewards in terms of career commitment, work meaningfulness and subsequent job satisfaction. 26 This study believes that a high level of career calling may enhance the effect of decent work on relative deprivation.…”
Section: Moderating Role Of Career Callingmentioning
confidence: 99%
“…Employees with higher levels of career calling have richer psychological resources, are better at self-regulation, and experience more meaning and passion, which allows them to adjust to their work environment. 49 This in turn allows them to align their cognitive behavior with the realization of their career calling 50 and become more committed to their career, 51 thus enhancing the moderating effect of decent work on relative deprivation. On the contrary, when employees have a low level of career calling, they may not feel motivated by public service or a sense of work accomplishment and pay more attention to such factors as income and work intensity.…”
Section: Moderating Role Of Career Callingmentioning
confidence: 99%